The The Effectiveness of Discovery-Inquiry Learning Strategy for Understanding Poetry Message - Gasong, Dina; Siregar, Eveline (Journal of Education Reseach and Evaluation, 2023)
In poetry reading contests, it was found that the contestants had not been able to show the correct expression in accordance with the message of the poem. This fact causes the message of poetry to not be understood. Choosing the right learning strategy can lead students to find the right message according to the text of the poem. Understanding the meaning of poetry in learning is very important in adapting to learning strategies. The right learning strategy for exploring the message in poetry is the Discovery-Inquiry Learning strategy. This study aimed to analyze the application of Discovery-Inquiry Learning strategies to understand the message of poetry. The subjects of this study were third semester students of Indonesian Language and Literature Education. The research method used was qualitative, with the following learning steps. The results of the study showed that by applying the find-investigation learning strategy, (1) students were able to find physical elements associated with mental elements. (2) students were motivated to study poetry, (3) students were able to understand the message of poetry by investigating the connotative meaning of repeated words or lines.